The Effect Of The Addition of Copper DB Killer On Yamaha Vixion 150cc Motorcycle on Exhaust Emissions: Pengaruh Penambahan DB Killer Tembaga Pada Knalpot Racing Motor Yamaha Vixion 150cc Terhadap Emisi Gas Buang - Wibowo, Herdianto Tri; Akbar, Ali Akbar (Procedia of Engineering and Life Science, 2023)
The addition of racing exhaust to a vehicle will greatly affect the quality of exhaust emissions. Racing exhausts that use the FreeFlow system which throws the remaining combustion gases out immediately without any deflection and catalyst in the racing exhaust. The addition of DB Killer uses nest-shaped copper material, besides reducing noise it also reduces excessive emissions and the material is easy to obtain, inexpensive, and has a simple manufacturing process. The advantage of DB Killer is that using a nest model copper plate catalyst material significantly reduces emissions compared to not using DB Killer. The DB Killer is installed at the end of a racing exhaust silencer and tested at different RPMs of 3500, 4500 and 5500. Tested using a gas analyzer to obtain CO, HC and CO2 values ​​for racing exhaust emissions without DB Killer and using a copper DB Killer. Obtaining the results of reducing exhaust emissions is much better and produces less noise. The result is a lower exhaust emission value because there is a DB Killer made of copper at the end of the exhaust silencer which can withstand emissions in the DB Killer which has a hollow design.